Determination of Internal Erosion and Permittivity of Biopolymer-Added Geosynthetic Clay Liners - Hakkı Oral Özhan (Doğal Afetler ve Çevre Dergisi)
Geosynthetic clay liner (GCL) can be used as a lining material in freshwater reservoirs due to its very low hydraulic conductivity. The high amount of water that can be collected on top of a GCL might force the bentonite in the GCL to be extruded out of the geotextiles and as a result, the sudden increase in the hydraulic conductivity might cause the GCL to loose its hydraulic capability. This interaction is defined as internal erosion. In this study, triaxial permeability tests were conducted on chitosan and Na carboxymethyl celluloseadded GCLs. These two biopolymers were added to the bentonite component of the GCLs with a content of 0.25, 0.5, 1, 2, 5 and 10% by dry weight respectively. Na and Ca bentonites were used in the GCLs and the GCLs that were placed over a rounded coarse gravel with a grain size of 37.5 mm, were tested at high hydraulic heads in order to observe internal erosion. This condition represents one of the worst-case scenarios. Test results indicated that all of the GCLs experienced internal erosion at a hydraulic head of 10 m. Furthermore, the permittivity values of the GCLs just before internal erosion, were measured and the effects of the biopolymers on the GCL’s hydraulic performance were investigated. According to the test results, 1% chitosan and 2% Na carboxymethyl cellulose addition to the bentonite component of the GCLs resulted in more than 2 orders of magnitude decrease in permittivity. Due to the results of this study, the usage of two different biopolymers that are environmentally friendly organic additives can be encouraged to be used as barriers in geoenvironmental application by decreasing the hydraulic conductivity of the lining material.